Therapeutic plasma exchange in Graves’ disease – A Case Report - Mamun, A B M Al; Islam, Kashfia; Karim, Tanzin Ara (Pulse, 2025)
Therapeutic plasma exchange (TPE) is one possible treatment for patients resistant to conventional antithyroid drugs or requiring urgent attention for thyrotoxicosis. We report a 26-yr-old man with thyrotoxicosis, ultimately attributed to Graves’ disease in whom antithyroid drug used initially was soon discontinued, due to agranulocytosis. Due to the agranulocytosis, antithyroid drugs were not an option, so radioactive iodine (RAI) treatment was the next resort. Unfortunately, the free thyroid hormone level was still elevated and euthyroid state was required prior to RAI treatment, so another strategy was needed to correct the thyroid function. So, we performed TPE to control the thyrotoxicosis. Pulse Volume 16, Issue 2 2024, P: 27-30